Evidence That Head and Body Lice on Homeless Persons Have the Same Genotype - Veracx, Aurélie; Rivet, Romain; McCoy, Karen D.; Brouqui, Philippe; Raoult, Didier (PloS one, 2012)
Human head lice and body lice are morphologically and biologically similar but have distinct ecologies. They were shown to have almost the same basic genetic content (one gene is absent in head lice), but differentially express certain genes, presumably responsible for the vector competence. They are now believed to be ecotypes of the same species (Pediculus humanus) and based on mitochondrial studies, body lice have been included with head lice in one of three clades of human head lice (Clade A). Here, we tested whether head and body lice collected from the same host belong to the same population by examining highly polymorphic intergenic spacers. This study was performed on lice collected from five homeless persons living in the same shelter in which Clade A lice are prevalent. Lice were individually genotyped at four spacer loci. The genetic identity and diversity of lice from head and body populations were compared for each homeless person. Population genetic structure was tested between lice from the two body regions and between the lice from different host individuals.We found two pairs of head and body lice on the same homeless person with identical multi locus genotypes. No difference in genetic diversity was found between head and body louse populations and no evidence of significant structure between the louse populations was found, even after controlling for a possible effect of the host individual. More surprisingly, no structure was obvious between lice of different homeless persons.We believe that the head and body lice collected from our five subjects belong to the same population and are shared between people living in the same shelter. These findings confirm that head and body lice are two ecotypes of the same species and show the importance of implementing measures to prevent lice transmission between homeless people in shelters.